2009
DOI: 10.1021/ol901662c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Peptide Linkers: Simultaneous Cyclization and Labeling

Abstract: Synthesis of novel peptide linkers was accomplished by monocarboxylation of 1,3,5-tris(bomomethyl)benzene with a wide variety of carboxylic acids in the presence of diisopropylethylamine. These reagents can be used to simultaneously cyclize and label peptides containing two cysteines. Many labels are compatible with this method including lipids, fluorescent groups, and biotin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…We and others (Dewkar, Carneiro, & Hartman, 2009; Timmerman et al, 2005) have shown that the peptide concentration for this reaction is optimal between 0.01 and 1 m M , but can also be achieved at higher concentrations. One of the byproducts encountered if the peptide is too concentrated is the cross-linked dimer.…”
Section: Applications Tips and Troubleshootingmentioning
confidence: 75%
“…We and others (Dewkar, Carneiro, & Hartman, 2009; Timmerman et al, 2005) have shown that the peptide concentration for this reaction is optimal between 0.01 and 1 m M , but can also be achieved at higher concentrations. One of the byproducts encountered if the peptide is too concentrated is the cross-linked dimer.…”
Section: Applications Tips and Troubleshootingmentioning
confidence: 75%
“…For cyclization, we focused on the well-established and robust bis-bromomethylbenzene chemistry, which covalently cyclizes peptides with two cysteines. 3335 The random position of the second cysteine allows the BRCA1 protein to “choose” from a variety of ring sizes or linear peptides for an optimum fit. Based on our previous work describing amino acid analogues that can be incorporated by substitution in ribosomal translation, 36 a group of six unnatural amino acids (Figure 1, Supporting Information Chart S1) were optimized for use together with the other 14 natural amino acids to make up the building blocks for the peptide selection (Supporting Information Figures S1–S5 and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…23 Inhibitors of the p53-HDM2 interaction reactivate p53 and are expected to induce apoptosis to malignant cells. 24 X-ray crystallographic study of the complex of peptide p53 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (SQETFSDLWKLLPEN), derived from the transactivation domain of p53, with HDM2 revealed that p53 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] formed a ahelical structure in binding and the hydrophobic residues (Phe19/Trp23/Leu26) interacted with the cleft on HDM2. 25 Peptide inhibitors and peptide mimetic compounds have been developed for regulating the p53-HDM2 interaction.…”
Section: Design Of Inhibitory Peptides Based On Yt1-s Analog For P53-mentioning
confidence: 99%
“…Cyclization methods with α,α′‐dibromoxylene and the derivatives have been successfully developed to constrain peptides . Although simultaneous cyclization and labeling of peptides with 1,3,5‐tris(bromomethyl)benzene was achieved, it required monoalkylation of the precursor linker before simultaneous cyclization and labeling . To develop a feasible method for introducing a variety of functional molecules to the cyclized peptides by using the CuAAC reaction, here we used 1,3‐di(bromomethyl)‐5‐propargyloxybenzene ( DBMPB ), originally synthesized for the intermediate to produce a linker for hyperbranched polymers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation